2013
DOI: 10.1021/ic4012718
|View full text |Cite
|
Sign up to set email alerts
|

Templated Non-Oxide Sol-Gel Preparation of Well-Ordered Macroporous (inverse opal) Ta3N5 Films

Abstract: Reactions of Ta(NMe2)5 and n-propylamine are shown to be an effective system for sol-gel processing of Ta3N5. Ordered macroporous films of Ta3N5 on silica substrates have been prepared by infiltration of such a sol into close-packed sacrificial templates of cross-linked 500 nm polystyrene spheres followed by pyrolysis under ammonia to remove the template and crystallize the Ta3N5. Templates with long-range order were produced by controlled humidity evaporation. Pyrolysis of a sol-infiltrated template at 600 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Firing at 600 °C leads to TaN while heating to 800 °C yields Ta 3 N 5 . 88 It is thus clear from the above that nanocrystals of the group 5 nitrides have not been convincingly obtained in colloidal form. While this is the first challenge for the future, the second challenge is to control the oxidation state and the polymorphism of these materials.…”
Section: Group 5 Metal Nitridesmentioning
confidence: 99%
See 1 more Smart Citation
“…Firing at 600 °C leads to TaN while heating to 800 °C yields Ta 3 N 5 . 88 It is thus clear from the above that nanocrystals of the group 5 nitrides have not been convincingly obtained in colloidal form. While this is the first challenge for the future, the second challenge is to control the oxidation state and the polymorphism of these materials.…”
Section: Group 5 Metal Nitridesmentioning
confidence: 99%
“…In 2013, a sol–gel pathway was demonstrated with Ta(NMe 2 ) 5 and n -propylamine. 88 Transamination occurs readily but the condensation appears to be slower than for titanium (see section on titanium nitride for details on transamination and condensation). Upon solvent evaporation a gel was formed.…”
Section: Group 5 Metal Nitridesmentioning
confidence: 99%
“…Reactions of transition metal amides with ammonia are usually poorly controlled, and a less reactive cross-linker such as a primary amine is necessary to achieve controlled sol-gel processing [28,224,225]. Löffelholz et al mixed boron, titanium, zirconium and tantalum dimethylamides with Si(NHMe)4 and achieved gelation by cross-linking with ammonia without a requirement for a catalyst [226,227].…”
Section: Incorporation Of Other Elements Under Ammonolytic Sol-gel Comentioning
confidence: 99%
“…58 Non-oxide sol-gel methods can be used to produce a range of morphologies including metal nitride powders, lms and porous structures. [59][60][61][62][63] We recently showed that sols based on Ti(NMe 2 ) 4 and n PrNH 2 could be used to coat nanocrystalline LiFePO 4 powders providing an effective conductive surface when the powders were incorporated into lithium battery cathodes. 64 Herein we use an adaptation of that process to coat carbon bres with the aim of exploiting a redox functionality in the coatings to provide increased capacitance.…”
Section: Introductionmentioning
confidence: 99%